Analysis of the Use of Word wall Learning Media in Informatics Subjects for Grade VII at Citra Bangsa Middle School, Kupang - Manu Gala, Vinsen Afrinto; Beatrice Sogen, Maria Magdalena; Bado, Mariana Wiwin; Sobeukum, Merty; Nauf, Dauf (JUPE : Jurnal Pendidikan Mandala, 2025)
This study to examine the implementation pf the wordwall learning media in the informatics subject at SMP Citra Bangsa Kupang, grade 7. The background of this research is the low student motivation and interest due to monotonous learning methods. The research used a qualitative approach with data collection techniques such as interviews and questionnaires. The result show that the use of wordwall had a positive impact on student’learning process. The media was considered fun, easy to access, and capable of increasing student motivation and engagement. Students expressed preference for wordwall-based quizzes over traditional ones. Teachers also observed Increased student participation during lessons. Therefore. Wordwall can be an effective, interactive, and engaging alternative media to be implemented in informatics and other subjects.